anonymous
  • anonymous
Ln (x+1) - Ln (x-1) = 3
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Use log properties and combine ln[(x+1)/(x-1)] = 3 raise both sides by e (x+1) / (x-1) = e^3 x+1 = e^3(x-1) x+1 = xe^3 - e^3 x-xe^3 = -e^3 - 1 x(1-e^3) = -e^3-1 x = (-e^3-1) / (1-e^3) Have a good day!
anonymous
  • anonymous
note that lna-lnb = ln(a/b) and lne^x=x ln(x+1)-ln(x-1)=3 ln((x+1)/(x-1))=lne^3 ((x+1)/(x-1))= e^3 ((x+1)/(x-1))(x-1) = e^3 (x-1) x+1 = (x-1)e^3 = xe^3 -e^3 x+1-xe^3=xe^3-e^3 -xe^3 x-xe^3+1-1=-e^3 -1 (1-e^3)x=-e^3-1 x=(-e^3-1)/(1-e^3)
anonymous
  • anonymous
Sorry that I am a bit slow

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

jhonyy9
  • jhonyy9
so what is equal continued x= -(e^3 +1)/(-(e^3 -1) = (e^3 +1)/(e^3 -1)
jhonyy9
  • jhonyy9
hope you like it !!!
jhonyy9
  • jhonyy9
yes i know but this is the final result
lgbasallote
  • lgbasallote
oh wait...thought expanding to cubey thingy makes difference..seems not

Looking for something else?

Not the answer you are looking for? Search for more explanations.